Effect of SIRS and sepsis on mortality in alcoholic hepatitis: A systematic review and meta-analysis - Jaruvongvanich, Veeravich; Sanguankeo, Anawin; Upala, Sikarin (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: Sepsis is frequently observed in patients with alcoholic hepatitis (AH) and is an important mortality predictor. Several studies have also identified systemic inflammatory response syndrome (SIRS) as a significant prognostic factor. The aim of this study was to systematically review and quantify the effect of SIRS and sepsis on mortality in patients with AH. Materials and Methods: MEDLINE and EMBASE were searched from its inception till January 2016. Participants in the included studies were adults with AH and those with developed SIRS or sepsis during hospitalization. We estimated the risk ratio (RR) with a 95% confidence interval (CI) of mortality by comparing participants with SIRS vs. non-SIRS and sepsis vs. non-sepsis. Results: Data were extracted from six studies involving 1,264 patients (of whom 507 had SIRS) and four studies involving 57,529 patients (of whom 1,449 had sepsis). SIRS and sepsis were both significantly associated with mortality with RRs of 2.7 (95% CI 1.74–4.14, I2=50%) and 2.8 (95% CI 1.58–4.93, I2=94%), respectively. Conclusion: Not only is sepsis associated with mortality but also SIRS. SIRS may be the initial trigger of cascade events leading to mortality in patients with AH. Identification of the key element of SIRS may thus provide a potential therapeutic target.